KEMAMPUAN MENERJEMAHAN TEKS ANALYTICAL EXPOSITION SISWA KELAS XII SMA - Putrawan, Gege Eka; Riadi, Bambang (Jurnal Pendidikan Progresif, 2016)
The Ability of Translating Analytical Exposition Text at Twelfth Grade of SMA. This study aimed at describing the ability of the twelfth grade students of SMA Negeri 1 Gadingrejo Pringsewu Academic Year 2015/2016 in translating an analytical exposition text from English into Indonesian. This is a qualitative descriptive research with a total sample of 50 students. The data were collected through a test in the form of translation work of an analytical exposition text. The results showed that in general the ability of the students in translating an analyticalexposition text from English into Indonesian of the twelfth grade students of SMA Negeri 1 Gadingrejo Pringsewu Odd Semester Academic Year 2015/2016 is categorized good with an average score of 76.2 Keywords: translating, translation, text, analytical exposition DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601